Competencias emprendedoras digitales desde una perspectiva de género en la Universidad de Los Andes de Colombia - Moreira Delgado, María Dayana (2025)
In a business landscape transformed by the digital age, digital entrepreneurial skills have become key factors for success. The objective of this research is to determine if there are significant differences in digital entrepreneurial competence between male and female students at the entrepreneurship center of the Universidad de los Andes in Colombia. It is a study with a quantitative, non-experimental approach with a descriptive design and correlational scope. 120 students from the entrepreneurship program were taken as the population, considering a non-probabilistic sampling for convenience, and a Student’s t-test was applied to evaluate the statistical significance of the variables. The study's results do not show significant differences in digital entrepreneurial competence between men and women. However, in the Opportunity Identification dimension, men showed a slightly higher average, while, in Action Planning, women had a marginally higher average. This finding suggests that, in the specific context of the Universidad de los Andes, both genders have a high level of digital entrepreneurial competence. The above could be related to the inclusive educational strategies and development opportunities that the University implements to promote gender equality in this area.